2015
DOI: 10.1097/bsd.0000000000000222
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Early Clinical and Radiographic Complications of Iliac Screw Fixation Versus S2 Alar Iliac (S2AI) Fixation in the Adult and Pediatric Populations

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 11 publications
1
59
1
3
Order By: Relevance
“…Shabtai et al [14] also reported that in patients with neuromuscular scoliosis, implant failure rate was lower and surgical revision was less frequent with SAI screws than with iliac screws. In other reports, the reoperation rate after iliac screw fixation was as high as 35%-48%, and lumbopelvic fixation using SAI screws reduced the need for reoperation by as much as 8.6%-14.5% [13,15,16]. Thus, SAI screws appear to have advantages over iliac screws in terms of reducing implant failure and lowering the rate of reoperation.…”
Section: Discussionmentioning
confidence: 79%
“…Shabtai et al [14] also reported that in patients with neuromuscular scoliosis, implant failure rate was lower and surgical revision was less frequent with SAI screws than with iliac screws. In other reports, the reoperation rate after iliac screw fixation was as high as 35%-48%, and lumbopelvic fixation using SAI screws reduced the need for reoperation by as much as 8.6%-14.5% [13,15,16]. Thus, SAI screws appear to have advantages over iliac screws in terms of reducing implant failure and lowering the rate of reoperation.…”
Section: Discussionmentioning
confidence: 79%
“…Different techniques for pelvic fixation exist and are associated with different complication rates. [12][13][14] Because this study was performed using CPT codes, only the general procedure was accounted for, so it was not possible to determine the effect of specific techniques used. Furthermore, patients were matched by total relative value units to account for case mix, fusion approach, and additional operative features such as pedicle subtraction osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on pelvic fixation have considered the differences in complications between different techniques for extension to the pelvis. [12][13][14] Others have been noncomparative investigations, focusing solely on outcomes. [15][16][17] To our knowledge, no study has used a large, multiinstitutional database to describe the risk profile for pelvic fixation in patients who undergo fusion for ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional sacropelvic fixation includes trans‐iliac bars and iliac and iliosacral screws. However, these require separate incisions for the use of offset connectors, thus increasing the surgical time and incidence of complications …”
Section: Discussionmentioning
confidence: 99%
“…O'Brien et al subsequently adapted it for use in minimally invasive applications . Ilyas et al found that S2AI technique is associated with significantly fewer clinical and radiographic complications in adult patients than the iliac screw technique . The S2AI technique for pelvic fixation is a modification of an S 2 alar screw driven through the sacroiliac articulation into the iliac wing.…”
Section: Discussionmentioning
confidence: 99%